Angled physical vapor deposition techniques for non-conformal thin films and three-dimensional structures. (12th February 2016) - Wang, Zhuoxian; West, Paul R.; Meng, Xiangeng; Kinsey, Nathaniel; Shalaev, Vladimir M.; Boltasseva, Alexandra
Abstract: Abstract : The field of nanophotonics has experienced a dramatic development in recent years, which requires ample candidate structures to achieve desirable functionalities. For many novel device designs in emerging field of transformation optics, optical metamaterials, and others, non-uniform and non-conformal thin films as well as three-dimensional (3D) structures are necessary to achieve advanced functionalities. Here, we report several techniques utilizing angled physical vapor deposition to obtain unique and complex 3D structures such as films with tapered thickness on planar substrates, tapered or uniform films on curved surfaces, and 3D nanorod arrays. These structures could enrich the existing practical design space for applications in nanophotonics and nanoelectronics.